The Effect of the Elaboration Likelihood Model on Purchase Intention: The Case of Live Streaming on Facebook and TikTok - Chanta-Atipong, Suchaya; Worapishet, Thirarat (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research aimed to study the effect of the Elaboration likelihood Model (ELM) on purchase intention via live streaming, with the Uses and gratification theory (U&G) as a moderator variable. The data were collected from 400 Thai people who had experience in purchasing products via live streaming via Facebook or TikTok. The data were analyzed using multiple regression. The results found that five factors from ELM, including real-time Q&A, urgency and scarcity, Information and details, Charisma and appeal, and entertainment, significantly influenced purchase intention during live streaming. As Social proof and honesty and transparency were not significantly influencing purchase intention. As for the moderator variables including information seeking, social interaction, personal identity, entertainment, and escapism, the relationship was found to have different effects in each consumer group. Article history: Received 18 March 2025 Revised 10 September 2025 Accepted 15 September 2025 SIMILARITY INDEX = 1.20 %